2017
DOI: 10.1002/2017ms001033
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous characterization of mesoscale and convective‐scale tropical rainfall extremes and their dynamical and thermodynamic modes of change

Abstract: The Superparameterized Community Atmosphere Model (SPCAM) is used to identify the dynamical and organizational properties of tropical extreme rainfall events on two scales. We compare the mesoscales resolved by General Circulation Models (GCMs) and the convective scales resolved by Cloud‐Resolving Models (CRMs) to reassess and extend on previous results from GCMs and CRMs in radiative‐convective equilibrium. We first show that the improved representation of subgridscale dynamics in SPCAM allows for a close agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 49 publications
8
55
1
Order By: Relevance
“…Additional condensation may occur if destabilization by the large‐scale flow pushes the system toward a different level of convective organization that makes the local environment ever so drier, thereby leading to ∂ t W ≪ 0 and invalidating the scaling approximation. In the case of SPCAM, individual CRMs often show an internally organized structure: Figure S9 shows that 70% of the local CRM rainfall is contained in one single subgrid‐scale rain event at locations of hourly extremes, and according to Figure in Fildier et al () the subgrid‐scale rainy columns span about a third of the domain at locations of GCM‐scale daily extremes. The internal structure of these extremes suggests that efficient suppression of condensation by detrainment of cloudy air is quite unlikely to occur.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Additional condensation may occur if destabilization by the large‐scale flow pushes the system toward a different level of convective organization that makes the local environment ever so drier, thereby leading to ∂ t W ≪ 0 and invalidating the scaling approximation. In the case of SPCAM, individual CRMs often show an internally organized structure: Figure S9 shows that 70% of the local CRM rainfall is contained in one single subgrid‐scale rain event at locations of hourly extremes, and according to Figure in Fildier et al () the subgrid‐scale rainy columns span about a third of the domain at locations of GCM‐scale daily extremes. The internal structure of these extremes suggests that efficient suppression of condensation by detrainment of cloudy air is quite unlikely to occur.…”
Section: Discussionsupporting
confidence: 83%
“…Because both scaling expressions are often used to quantify contributions to changes in extreme rainfall with climate change, we can use results from the previous section to assess the ability of these formulas to characterize increases in the strength of individual extreme events. We will focus on the FT scaling in this section because it better approximates extreme rainfall intensities (section ) and allows for a more complete decomposition into dynamic and thermodynamic contributions (Fildier et al, ).…”
Section: Implications For Fractional Changes In Extreme Precipitationmentioning
confidence: 95%
See 1 more Smart Citation
“…Trenberth et al () first argued that heavy precipitation intensity should increase due to the increasing atmospheric moisture at the rate of ~7%/K and there must be a decrease in light‐moderate precipitation and/or a decrease of total precipitation frequency. Fildier et al () showed that the extreme precipitation intensity increases by ~7%/K using the Community Atmosphere Model with superparameterization. Intensified heavy precipitation have been observed across many regions of the world (Alexander, ; Donat et al, ; Fischer & Knutti, ; Karl et al, ; Kunkel & Frankson, ; Westra et al, ), especially in the humid regions (Donat et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the changes in PE in urban areas with warming climate can be valuable in mitigating the adverse social and financial consequences (Fildier et al, ). Since PE occur when air is close to saturation, the Clausius‐Clapeyron (C‐C) relationship is used to explain an increase in the observed and projected extreme precipitation with the rise in air temperature (Ali & Mishra, ; Lenderink & Van Meijgaard, ; Mishra, Smoliak, et al, ; Wasko & Sharma, ; Wasko et al, , ; Westra et al, ).…”
Section: Introductionmentioning
confidence: 99%